Aggregate Bankruptcy Probabilities and Their Role in Explaining Banks' Loan Losses - Olga Andreeva (Norges Bank, 2004)
Increased competition forces banks to narrow lending margins and at the same time relaxed lending standards worsen the pool of borrowers. To preserve sound banking system it is important task to monitor credit risk as one of the dominant factors leading to bank failures and financial vulnerability. Norwegian banks traditionally have a large share of loans to nonfinancial enterprises in their investment portfolios, and we focus on risk related to loans provided to limited liability enterprises. By combining statistics on loans to Norwegian industries and regions and bankruptcy probabilities for individual corporate borrowers, we construct a proxy reflecting risk profile of the banks' loan portfolios. Aggregation within industries and counties provides a bank-level panel of risk indicators, which are used to estimate banks' loan losses during the period 1988 - 2001. Constructed aggregate bankruptcy probabilities prove to be meaningful measures, which explain loan losses if we control for the macroeconomic and bank specific factors.
hdl:11250/2498535
Keywords: G21; C81; 330; bank losses; bankruptcy probabilities; aggregation